1994
DOI: 10.1095/biolreprod50.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Relaxin from Lactating Bitches to their Offspring Via Suckling1

Abstract: The 6-kDa polypeptide hormone relaxin (Rlx) has been identified in human and bovine milk, and we recently reported its presence in canine milk. We postulated that Rlx might be transferred via suckling to the newborn pups, where, by virtue of its known effects to increase the distensibility of the pelvic connective tissues, it could play a role in causing the excessive laxity of the capsule and ligaments of the coxofemoral joint that precedes the development of hip dysplasia in genetically predisposed animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 26 publications
5
50
1
2
Order By: Relevance
“…Studies in other species indicate that relaxin of maternal origin could be an important source of the hormone in the neonate by way of ingestion of colostrum and milk. Relaxin is detectable in human (Eddie et al 1989) and canine (Goldsmith et al 1994) colostrum and milk, and mammary tissue has been suggested as a local source of relaxin (Tashima et al 1994). Like other peptide growth factors in milk, relaxin may contribute to early neonatal development (Burrin et al 1997, Anderson et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other species indicate that relaxin of maternal origin could be an important source of the hormone in the neonate by way of ingestion of colostrum and milk. Relaxin is detectable in human (Eddie et al 1989) and canine (Goldsmith et al 1994) colostrum and milk, and mammary tissue has been suggested as a local source of relaxin (Tashima et al 1994). Like other peptide growth factors in milk, relaxin may contribute to early neonatal development (Burrin et al 1997, Anderson et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin (RLX), a prototypical milk-borne peptide hormone , is found in the colostrum of several species including humans (Eddie et al 1989), dogs (Goldsmith et al 1994), rats ), and pigs (Yan et al 2006). Immunoreactive RLX is detectable in the systemic circulation of newborn pigs only if they are allowed to nurse (Yan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…our model it would be unaffected unless the pups take up RLFi during suckling. It has been shown in beagles that the hormone relaxin reaches the pups through the milk (Goldsmith et al 1994). Although RLFi effectively inhibits intra-abdominal migration of the testis in a dose-dependent manner, complete inhibition as described for the RLF (Insl3; Nef & Parada 1999, Zimmermann et al 1999 or GREAT (Lgr8; Overbeek et al 2001) knockout mouse has not been observed.…”
Section: Discussionmentioning
confidence: 98%